2021
DOI: 10.1371/journal.pone.0252417
|View full text |Cite|
|
Sign up to set email alerts
|

Development of the Bristol Rabbit Pain Scale (BRPS): A multidimensional composite pain scale specific to rabbits (Oryctolagus cuniculus)

Abstract: A species-specific composite pain scale is a prerequisite for adequate pain assessment. The aim of this study was to develop a multidimensional pain scale specific to rabbits (Oryctolagus cuniculus) called the Bristol Rabbit Pain Scale (BRPS). The scale was developed over five phases using a unique combination of methods: focus groups and behavioural observation. The first two phases aimed at identifying descriptors to describe a rabbit in pain, and then reducing their number, both using focus groups. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 45 publications
1
37
0
1
Order By: Relevance
“…Internal consistency showed that the scale items behave in the same way, with a concomitant increase or decrease in their scores according to the intensity of pain [ 50 ]. Our values were similar but a little lower than the BRPS [ 20 ].…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Internal consistency showed that the scale items behave in the same way, with a concomitant increase or decrease in their scores according to the intensity of pain [ 50 ]. Our values were similar but a little lower than the BRPS [ 20 ].…”
Section: Discussionsupporting
confidence: 69%
“…This reflects the need to submit new instruments to strict statistical refinement criteria to increase its discriminatory capacity and avoid the insertion of unnecessary items. The RPBS items are similar to those approved in five phases during the creation of the BRPS [ 20 ], a scale developed in parallel and published after completion of the current study. The RPBS is based on strict and complete behaviour selection criteria, which confirms its importance in identifying pain in the species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations